Restoring BMPRII functions in pulmonary arterial hypertension: opportunities, challenges and limitations. (1st February 2017) - Guignabert, Christophe; Bailly, Sabine; Humbert, Marc
ABSTRACT: Introduction: Pulmonary arterial hypertension (PAH) is a cardiopulmonary disorder in which mechanical obstruction of the pulmonary vascular bed is largely responsible for the rise in pulmonary arterial pressures. The discovery of heterozygous BMPR2 germline mutations as critical predisposing factors together with a remarkable progress in our understanding of the pathogenic mechanisms have helped identify the significant and complex roles of the BMPRII axis in PAH. However, their precise contributions to the condition are still incompletely understood. Areas covered: This review aims to assemble and discuss the cellular actions of BMPs together with the possible clinical applications and prospects for their use in the near future. Expert opinion: Although major advances have been made, several questions remain unanswered regarding development of efficacious therapies targeting the BMPRII axis in PAH. Specifically, the reasons why BMPRII signaling is reduced in PAH and how the alterations influence or even drive the pathogenesis need to be understood. Because the BMPRII axis is ubiquitously expressed and exhibits a wide variety of functions in organ regeneration and homeostasis, a better understanding of the overall risk-benefit ratio of these strategies with long-term follow-up is needed. This knowledge will lay the foundation for discovery of innovative therapeutics for PAH.